7, 18, 29, 40, 51

Supposedly we take the above-stated sequence and find its nth term. Now since we have already identified that this sequence has a common difference, we know that it is a geometric sequence, hence we can easily use the below-mentioned formula.

Nth term Formula= a + (n-1)d

a= first term in the sequence

d= common difference

n= number of terms

In our case, a= 7, d=11. but n is not identified, so you just plug in the values in the above-mentioned formula.

Nth term= 7 + (n-1) 11

= 7 + 11n - 11

= 11n - 4